Comparison of waist-height ratio and other obesity indices in the prediction of diabetic peripheral neuropathy - Lawal, Yakubu; Mshelia-Reng, Rifkatu; Omonua, Special O.; Odumodu, Kenechukwu; Shuaibu, Ramatu; Itanyi, Ukamaka D.; Abubakar, Amina I.; Kolade-Yunusa, Hadijat O.; Songden, Zumnan D.; Ehusani, Caleb O.; Adediran, Olufemi; Anumah, Felicia E. (Frontiers in Nutrition, 2022)
Background Waist-height ratio (WHtR) is increasingly being studied as a simple and effective measure of central obesity. Reports have shown that WHtR is a better predictor of hypertension, diabetes, and cardiovascular diseases when compared to traditional obesity indices like body mass index (BMI), waist circumference (WC), and waist-hip ratio (WHR). This study is therefore aimed at comparing WHtR with other obesity indices in the prediction of peripheral neuropathy in persons with diabetes mellitus (DM). Methodology One thousand and forty persons with DM were enrolled following consent. Relevant details of history were obtained, followed by physical examinations. Data were analyzed using IBM-SPSS version 23. Logistic regression was used to compare the odds ratio of obesity indices in the prediction of peripheral neuropathy. The level of significance used was p = 0.05. Results Logistic regression showed that WHtR had the highest odds ratio (OR) for the prediction of “probable” diabetic peripheral neuropathy (OR 9.11, 95% CI 3.07–47.97, p = 0.002), followed by WC (OR 2.01, 95% CI 1.09–4.05, p = 0.004), and BMI (OR 1.26, 95% CI 1.00–3.99, p = 0.019) after correction for age; systemic hypertension; duration of DM; control of SBP, DBP, HbA1c, FPG, and 2HrPP. Conclusion WHtR has the highest odds ratio in the prediction of “probable” diabetic peripheral neuropathy in both genders, followed by WC in the males and BMI in the females.